Inflammation and Mental Health Disorders: Immunomodulation as a Potential Therapy for Psychiatric Conditions - Safari, Hanieh; Mashayekhan, Shohreh (Current Pharmaceutical Design, 2023)
Mood disorders are the leading cause of disability worldwide and their incidence has significantly increased after the COVID-19 pandemic. Despite the continuous surge in the number of people diagnosed with psychiatric disorders, the treatment methods for these conditions remain limited. A significant number of people either do not respond to therapy or discontinue the drugs due to their severe side effects. Therefore, alternative therapeutic interventions are needed. Previous studies have shown a correlation between immunological alterations and the occurrence of mental health disorders, yet immunomodulatory therapies have been barely investigated for combating psychiatric conditions. In this article, we have reviewed the immunological alterations that occur during the onset of mental health disorders, including microglial activation, an increased number of circulating innate immune cells, reduced activity of natural killer cells, altered T cell morphology and functionality, and an increased secretion of pro-inflammatory cytokines. This article also examines key studies that demonstrate the therapeutic efficacy of anti-inflammatory medications in mental health disorders. These studies suggest that immunomodulation can potentially be used as a complementary therapy for controlling psychiatric conditions after careful screening of candidate drugs and consideration of their efficacy and side effects in clinical trials.
Keywords: anxiety